Total chemical synthesis of PSMA-11: API for 68Ga-PSMA-11 used for prostate cancer diagnosis - K.S. Ajish Kumar; Anupam Mathur (Elsevier, 2021)
The imaging of prostate tumours by targeting Prostate Specific Membrane Antigen (PSMA), using binding tracer, 68Ga-PSMA-11, offer lots of promises for specific detection of prostate associated malignancies. The popularity of 68Ga-PSMA-11 as a radioligand tool for prostate cancer diagnosis has gained a major boost upon its FDA approval in December 2020. Development of an economically benign protocol for the synthesis of PSMA-11, using solution phase method, is particularly important to get a better access to this highly important and expensive Active Pharmaceutical Ingredient (API). The PSMA-11 synthesized using the protocol presented here, involves the use of a flow reactor based catalytic hydrogenation as the key step. Using the method portrayed, PSMA-11 with purity >99.5% was achieved, while, radiolabelling with 68Ga afforded 68Ga-PSMA-11 with radiochemical purity >95%, which is appropriate for imaging applications.